Peningkatan Pendapatan Kemplang Marmus melalui Marketing Produk dan Pengelolaan Keuangan - Eni Cahyani; Efrina Masdain; Bora Alviolesa; M. Syahril; Widi Samsudin (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service is aimed at Micro, Small and Medium Enterprises (MSMEs) Kemplang Marmus Tanjung Raja, Ogan Ilir Regency, South Sumatra. This technical guidance (Bimtek) activity aims to introduce marketing elements, especially the product itself, namely Kemplang tunu. Continued by increasing knowledge regarding the calculation of production costs (HPP) and simulation of production cost calculations. This activity involves students who carry out Real Work Lectures (KKN) together with field supervisors. After identifying the problem, it was agreed that the problem was that Kemplang Marmus was still constrained by packaging so that its marketing was unable to be present in certain segments and had not calculated the production cost, this made it difficult for MSMEs to determine the right competitive price. Based on the problems above, a product marketing and financial knowledge training was carried out. The training was carried out in 2 stages, namely technical guidance starting from increasing knowledge of product packaging, designing logos on primary and secondary packaging. The activity was continued with a simulation of calculating the production cost for 1 3/4 kg package.